Evaluation of a passive exoskeleton for static upper limb activities. (July 2018) - Huysamen, Kirsten; Bosch, Tim; de Looze, Michiel; Stadler, Konrad S.; Graf, Eveline; O'Sullivan, Leonard W.
Abstract: The aim of this study was to evaluate the effect of a passive upper body exoskeleton on muscle activity, perceived musculoskeletal effort, local perceived pressure and subjective usability for a static overhead task. Eight participants (4 male, 4 female) held a load (0 kg and 2 kg) three times overhead for a duration of 30 s each, both with and without the exoskeleton. Muscle activity was significantly reduced for the Biceps Brachii (49%) and Medial Deltoid (62%) by the device for the 2 kg load. Perceived effort of the arms was significantly lower with the device for the 2 kg load (41%). The device did not have a significant effect on trunk or leg muscle activity (for the 2 kg load) or perceived effort. Local perceived pressure was rated below 2 (low pressure levels) for all contact areas assessed. Half of the participants rated the device usability as acceptable. The exoskeleton reduced muscle activity and perceived effort by the arms, and had no significant negative effect on the trunk and lower body with regards to muscle activity, perceived effort and localised discomfort. Highlights: A passive upper body exoskeleton for static overhead tasks was assessed. Muscle activity was reduced for the Biceps Brachi by 49% and the Media Deltoid by 62%. There was no significant negative effects on the trunk and lower body variables studied. Half of the users rated the usability as acceptability. The study highlights aspects of exoskeleton design to be targeted for user acceptance.